Biosensor Based on a Nanowire Field-effect Transistor for the Determination of Prostate Specific Antigen. (2017) - Rubtsova, Maya; Presnova, Galina; Presnov, Denis; Krupenin, Vladimir; Grigorenko, Vitaly; Egorov, Alexey
Abstract: We report about a label-free and fast assay based on nanowire field-effect transistor (NW FET) for determination of PSA in human serum. Functionalization of NWs was performed by a new method using 5 nm gold nanoparticles (GNPs), which provides oriented covalent attachment of antibody half-fragments via their thiol groups. We use the GNPs to increase the effective surface-to-volume ratio of the silicon nanowires, which resulted in higher sensitivity to pH and improved electrical performance of the biosensors. NW FETs demonstrated high sensitivity and the widest range of detectable PSA concentrations. The presented biosensor was applied to human serum samples with different PSA content, yielding promising results for use in real sample assessment. The sensitivity achieved by the biosensor was 2 orders of magnitude higher than the well-established ELISA method.